Electricity and hydrogen production by cogeneration system applied in a fuel station in Brazil: Energy analysis of a combined SOFC and ethanol steam reforming model - Cordaro, P. G.; Braga, B. L. [UNESP]; Corotti, D.; Gallego, A. G.; Silveira, J. L. [UNESP] (Elsevier, 2024)
A model is presented that hydrogen and electricity are cogenerated by a compact system, regarding operational integration of units of SOFC and Ethanol reformer. This is a model of a simultaneously production of electricity and hydrogen to be applied and allocated strategically in fuel stations, considering the Brazilian conditions that such fuel stations follow marketing and logistics premises that allow to be regularity provided with ethanol biofuel as well are usually near to the consumers. The strategic is the use of the wide network of fuel stations that generally has relevant locations such as urban centers and highways for electricity and hydrogen supply. The objective refers to direct green-hydrogen usage after the processing of ethanol steam reforming, mitigating the usual technical and economics difficult and limitations related to storage and transportation of high volumes of hydrogen that alternatively could be accomplished with ethanol and water, using the proposed model. Concurrently, the same fuel stations would be a green-hydrogen provider, contributing to the reduction of pollution by using ethanol as a biofuel already extremely applied over all the Brazilian territory, attempting to the demands needed. The main novelty of this model refers to combination of three characteristics: (i) high heat produced by the SOFC that could be provided as the energy required for the (ii) endothermic Ethanol reforming, and this fuel is already used throughout (iii) Brazilian territory in fuel stations, which startup to offering also hydrogen and electricity as new products. The full study of this model consists in two papers, that in this first work is presented the thermodynamic analysis, aiming to identify the potential of the energy integration specially related to the SOFC and Reformer functionalities, as a technical feasibility validation. The conclusion of the theoretical results regarding mathematical modelling demonstrates this feasibility, indicating the existence of a minimum energy parity required between SOFC and Ethanol reformer.
Keywords: Electricity-generation; Ethanol steam reforming; Green-hydrogen; SOFC; Thermodynamic modeling of cogeneration